2016
DOI: 10.1016/j.jns.2016.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported physical activity in essential tremor: Relationship with tremor, balance, and cognitive function

Abstract: Background Physical inactivity may be the result of medical comorbidities. Inactivity itself may also lead to important health consequences, especially in older patients. Essential tremor (ET) patients may have a variety of physical and cognitive problems that could detrimentally impact on level of physical activity. Yet, to our knowledge, there have been no studies of physical activity in these patients. Methods Self-reported physical activity was assessed using the Physical Activity Scale for the Elderly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Of these, only one paper 9 reported that duration of ET, in addition to age, was correlated with balance impairments. In contrast, seven papers 6,7,8,11,22,41,42 did not find a significant correlation of balance impairment with the duration of ET, and two papers 10,20 did not report on this relationship.…”
Section: Are Balance and Gait Problems In Et Simply Related To Advanced Age?mentioning
confidence: 74%
See 2 more Smart Citations
“…Of these, only one paper 9 reported that duration of ET, in addition to age, was correlated with balance impairments. In contrast, seven papers 6,7,8,11,22,41,42 did not find a significant correlation of balance impairment with the duration of ET, and two papers 10,20 did not report on this relationship.…”
Section: Are Balance and Gait Problems In Et Simply Related To Advanced Age?mentioning
confidence: 74%
“…11 Lower balance confidence, and falls were associated with reduction in self-reported physical activity. 42 These results indicate that balance impairments not only limit functional activity, but may lead to reduced physical activity. The functional importance of balance impairment was highlighted in a recent study, which reported that impairment on the tandem walk test was a significant predictor of mortality in ET patients.…”
Section: What Are the Functional Consequences Of Balance And Gait Impairments?mentioning
confidence: 92%
See 1 more Smart Citation
“…Besides older age, additional variables have yet to be identified as predictors of cognitive decline in ET (12). In one cross-sectional study of participants with ET, an association was identified between lower levels of physical activity and poorer performance on the Montreal Cognitive Assessment (MOCA), a common measure of global cognition (13). Similarly, lower physical activity has been identified as a longitudinal predictor of conversion to MCI (14) and dementia (15)(16)(17)(18) in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Among the latter are cognitive impairments (Benito-Leon & Louis, 2013;Janicki, Cosentino, & Louis, 2013;Louis, 2010;Louis & Rao, 2014b;Mameli et al, 2013;Sinoff & Badarny, 2014), such as reductions in attention, executive function, visuospatial processing, and memory (Gasparini et al, 2001;Janicki et al, 2013;Kim et al, 2009;Lombardi, Woolston, Roberts, & Gross, 2001;Tröster et al, 2002); and increased risk of mild cognitive impairment (MCI) and dementia (Benito-León, Louis, Bermejo-Pareja, & NEDICES Study Group, 2006a, 2006b; Benito-León, Louis, Mitchell, & Bermejo-Pareja, 2011;Bermejo-Pareja, Louis, Benito-León, & NEDICES Study Group, 2007;Louis, Benito-León, Vega-Quiroga, Bermejo-Pareja, & NEDICES Study Group, 2010; Correspondence and reprint requests to: Stephanie Cosentino; Columbia University Medical Center, 630 West 168th Street; P&S Mailbox 16; NY, NY 10032; E-mail: sc2460@cumc.columbia.edu Thawani, Schupf, & Louis, 2009), deficits which are reflected in functional imaging studies, with abberant network connectivity observed to be associated with tremor features and cognitive dysfuncton (Benito-León et al, 2015). Cognitive dysfunction that occurs in ET, even when mild, is accompanied by a range of functional consequences (Louis et al, 2010(Louis et al, , 2016(Louis et al, , 2017Rao, Gillman, & Louis, 2014;Rao, Uddin, Gillman, & Louis, 2013), thereby highlighting its importance.…”
Section: Introductionmentioning
confidence: 99%